HDL cholesterol, apolipoproteins, and cardiovascular risk in hemodialysis patients - Silbernagel, Günther; Genser, Bernd; Grammer, Tanja B.; Ritz, Eberhard; März, Winfried (Journal of the American Society of Nephrology, 2015)
High concentrations of HDL cholesterol are considered to indicate efficient reverse cholesterol transport and to protect from atherosclerosis. However, HDL has been suggested to be dysfunctional in ESRD. Hence, our main objective was to investigate the effect of HDL cholesterol on outcomes in maintenance hemodialysis patients with diabetes. Moreover, we investigated the associations between the major protein components of HDL (apoA1, apoA2, and apoC3) and end points. We performed an exploratory, post hoc analysis with 1255 participants (677 men and 578 women) of the German Diabetes Dialysis study. The mean age was 66.3 years and the mean body mass index was 28.0 kg/m2. The primary end point was a composite of cardiac death, myocardial infarction, and stroke. The secondary end point included all-cause mortality. The mean duration of follow-up was 3.9 years. A total of 31.3% of the study participants reached the primary end point and 49.1% died from any cause. HDL cholesterol and apoA1 and apoC3 quartiles were not related to end points. However, there was a trend toward an inverse association between apoA2 and all-cause mortality. The hazard ratio for death from any cause in the fourth quartile compared with the first quartile of apoA2 was 0.63 (95% confidence interval, 0.40 to 0.89). The lack of an association between HDL cholesterol and cardiovascular risk may support the concept of dysfunctional HDL in hemodialysis. The possible beneficial effect of apoA2 on survival requires confirmation in future studies.